Consumo de bebidas azucaradas por niños en edad escolar (2020)
Purpose - To transmit knowledge that helps children and parents to understand in a simple, clear and fun way about the effects of sugary drinks. Design/methodology/approach - There are different design tools to take as a guide so that the research is classified in different ways taking quantitative and qualitative approaches. For this study, the type of descriptive research was preferred as it is related to the reality of the actors. selected. This type of study can be accompanied by interviews with design methods such as those mentioned below. Findings - With the purpose of generating fun, easy and clear means to inform children of the characteristics and consequences generated by the consumption of ultra-processed foods, the importance of creating related experiences in the school environment is taken into account. It is important to create a bond between children and parents; propose activities that intervene in the child's natural environment, raise awareness, since, when choosing food in the supermarket, some are influenced by the demands of their children.